Development of Learning Modules for Electric Power Plant Machinery for Class XI Phase F of Electric Power Plant Engineering Expertise Program in Vocational Schools - Luhur Adi Prasetya; Heru Wahyu Herwanto; Yoto Yoto (IJECA (International Journal of Education and Curriculum Application), 2024)
The Power Plant Engineering program at SMK aims to equip students with technical skills in operating machinery, diagnosing faults, and installing control equipment. However, observations at SMK Brantas Karangkates showed that the materials taught were not in accordance with the Merdeka Curriculum and the existing learning modules were not comprehensive enough. To address this problem, a new learning module was developed through Sugiyono's Research and Development model approach with an additional product development phase. The validity of the module was evaluated by two experts, a lecturer from State University of Malang who specializes in Learning Media and Power Plant Engineering, and a senior teacher from SMK Brantas Karangkates. The experts assessed the module from the aspects of content, language, presentation, and graphics, with excellent validation results: content 93.7%, language 87.3%, presentation 100%, and graphics 96.1%, with an average score of 94.3%. The limited trial with 10 grade XI students resulted in a score of 76%, indicating the need for revision. After revisions were made, the final trial with 64 students yielded a score of 93.6%, indicating that the module was highly valid and effective in improving the learning process.